Evaluation of soil quality of a coal mine affected forest at Changki, Nagaland, India - Semy, Khikeya; Singh, M. R.; Vats, Nishant (Journal of Environmental Engineering and Landscape Management, 2021)
The present study was conducted at a coal mining affected forest and a non-affected forest to analyze the seasonal changes in soil physico-chemical properties, incorporate additive and weighted soil quality index (SQI) to determine the soil quality and check the affected forest soil pollution status. Comparative SQI shows that the non-affected forest presented higher SQI in all the seasons (winter, spring, summer and autumn). However, in both the forest the seasonal additive and weighted SQI was categorised as autumn > summer > spring > winter and the overall SQI of the soil depth was ranked as 0–10 > 10–20 > 20–30 cm. The Single pollution index (PI) points out that cadmium (Cd) was the main potential contributor to soil pollution while the Pollution load index (PLI) and Nemerow integrated pollution index (NIPI) revealed moderate soil pollution status. The result summarized that coal mining activities can elevate soil deterioration rate, such as loss in soil organic carbon, reduction in nutrient availability, and slowing down the rejuvenating process of forest soil.